Chondrule Formation by the Jovian Sweeping Secular Resonance - Gong, Munan; Zheng, Xiaochen; Lin, Douglas N. C.; Silsbee, Kedron; Baruteau, Clement; Mao, Shude (The Astrophysical journal, 2019)
Chondrules are silicate spheroids found in meteorites, and they serve as important fossil records of the early solar system. In order to form chondrules, chondrule precursors must be heated to temperatures much higher than the typical conditions in the current asteroid belt. One proposed mechanism for chondrule heating is the passage through bow shocks of highly eccentric planetesimals in the protoplanetary disk in the early solar system. However, it is difficult for planetesimals to gain and maintain such high eccentricities. In this paper, we present a new scenario in which planetesimals in the asteroid belt region are excited to high eccentricities by the Jovian sweeping secular resonance in a depleting disk, leading to efficient formation of chondrules. We study the orbital evolution of planetesimals in the disk using semi-analytic models and numerical simulations. We investigate the dependence of eccentricity excitation on the planetesimal's size, as well as the physical environment and the probability for chondrule formation. We find that 50-2000 km planetesimals can obtain eccentricities larger than 0.6 and cause effective chondrule heating. Most chondrules form in high-velocity shocks, in low-density gas, and in the inner disk. The fraction of chondrule precursors that become chondrules is about 4%-9% between 1.5 and 3 au. Our model implies that the disk depletion timescale is τdep 1 Myr, comparable to the age spread of chondrules, and that Jupiter formed before chondrules, no more than 0.7 Myr after the formation of calcium aluminum inclusions.